Flexible Bench-Scale Recirculating Flow CPC Photoreactor for Solar Photocatalytic Degradation of Methylene Blue Using Removable TiO2 Immobilized on PET Sheets - Doaa M. EL-Mekkawi; Norhan Nady; Nourelhoda A. Abdelwahab; Walied A. A. Mohamed; M. S. A. Abdel-Mottaleb (International Journal of Photoenergy)
TiO2 immobilized on polyethylene (PET) nonwoven sheet was used in the solar photocatalytic degradation of methylene blue (MB). TiO2 Evonik Aeroxide P25 was used in this study. The amount of loaded TiO2 on PET was approximately 24%. Immobilization of TiO2 on PET was conducted by dip coating process followed by exposing to mild heat and pressure. TiO2/PET sheets were wrapped on removable Teflon rods inside home-made bench-scale recirculating flow Compound Parabolic Concentrator (CPC) photoreactor prototype (platform 0.7 × 0.2 × 0.4 m3). CPC photoreactor is made up of seven low iron borosilicate glass tubes connected in series. CPC reflectors are made of stainless steel 304. The prototype was mounted on a platform tilted at 30°N local latitude in Cairo. A centrifugal pump was used to circulate water containing methylene blue (MB) dye inside the glass tubes. Efficient photocatalytic degradation of MB using TiO2/PET was achieved upon the exposure to direct sunlight. Chemical oxygen demand (COD) analyses reveal the complete mineralization of MB. Durability of TiO2/PET composite was also tested under sunlight irradiation. Results indicate only 6% reduction in the amount of TiO2 after seven cycles. No significant change was observed for the physicochemical characteristics of TiO2/PET after the successive irradiation processes.